Intelligent task scheduling for computational grid - Abdullah, Abdul Hanan (2012)
A computational grid is a loose network of computers linked to perform grid computing. In a computational grid, a large computational task is divided up among individual machines, which run calculations in parallel and then return results to the original computer.